Relation of lymphopenia to comorbidity burden and its prognostic value in patients with acute decompensated heart failure with preserved left ventricular ejection fraction: a multicentre study. (3rd October 2022) - Tamaki, S; Nagai, Y; Shutta, R; Masuda, D; Yamashita, S; Seo, M; Yamada, T; Yano, M; Hayashi, T; Yasumura, Y; Hikoso, S; Sotomi, Y; et al.
Abstract: Background: Systemic inflammation resulting from comorbidities is postulated to play a central role in the pathophysiology of heart failure (HF) with preserved ejection fraction (HFpEF). Lymphopenia is a common manifestation of systemic inflammation and a prognostic factor in patients with HF. However, the association of lymphopenia with the comorbidity burden is unknown, and its prognostic value in patients with HFpEF admitted due to acute decompensated heart failure (ADHF) also remains elusive. Purpose: We sought to clarify the relation of lymphopenia with the comorbidity burden, as well as its prognostic value and complementarity with the Get with the Guidelines-Heart Failure (GWTG-HF) risk score in ADHF patients with HFpEF. Methods: Patients' data were extracted from the Prospective mUlticenteR obServational stUdy of patIenTs with Heart Failure with Preserved Ejection Fraction (PURSUIT-HFpEF), which is a prospective multicentre registry for patients with ADHF with a LVEF ≥50%. We analysed data of patients admitted between June 2016 and December 2020 who survived to discharge. The total lymphocyte count (per μL) and GWTG-HF risk score were obtained on admission, as previously reported. Comorbidity burden was defined as the number of comorbidities from the following: atrial fibrillation, hypertension, diabetes mellitus, coronary artery disease, chronic kidney disease, chronic obstructive pulmonary disease, anaemia, and obesity. The study endpoint was all-cause death. Results: Over a median follow-up of 417 days, 181 of the 1013 included patients died. The proportion of patients with a total lymphocyte count in the lowest tertile was increasing with the increase in comorbidity burden (Figure 1). In the multivariate Cox analysis, a total lymphocyte count in the intermediate (hazard ratio [HR] 1.55, 95% confidence interval [CI] 1.00–2.41, p=0.0486) and lowest tertile (HR 2.23, 95% CI 1.47–3.38, p=0.0002) was independently associated with all-cause death. There was a significant difference in the all-cause death rate among the groups stratified by total lymphocyte count tertile (Figure 2). The total lymphocyte count had a higher C-statistic value (0.627) for the prediction of all-cause death than the GWTG-HF risk score, and the C-statistic value of the GWTG-HF risk score was improved when the total lymphocyte count was added (0.613 to 0.636, p=0.0260). Conclusions: Lymphopenia was significantly associated with comorbidity burden. Furthermore, it was a useful marker of poor prognosis in hospitalised patients with acute HFpEF and was shown to be complementary to the contemporary HF prognostic score. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Roche Diagnostics K.K.Fuji Film Toyama Chemical Co. Ltd.